(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: This study aimed to describe the etiologies and treatment outcomes of indirect hyperbilirubinemia in neonates at Quang Ninh Obstetrics and Pediatrics Hospital from January 1, 2021, to August 31, 2023. Methods: A descriptive case-series study combining retrospective and prospective data collection was conducted on 284 neonates diagnosed with indirect hyperbilirubinemia. Results: Among the 284 neonates, males accounted for 56.7%; 77.8% were full-term, 22.2% preterm, and 21.8% had low birth weight. Jaundice was detected within the first 72 hours of life in 91.2% of cases. Neonatal infection was the most common cause (37.3%), followed by maternal–fetal blood group incompatibility (32.4%), glucose-6-phosphate dehydrogenase (G6PD) deficiency (4.6%), and congenital hypothyroidism (1.1%); in 37.7% of cases, no definitive cause was identified. Phototherapy alone was administered in 61.6% of cases, while 38.4% required combination therapies, and 3.2% underwent exchange transfusion. Neonates with maternal–fetal blood group incompatibility had a 7.82-fold higher risk of requiring exchange transfusion compared to those without incompatibility (p = 0.012). Conclusion: Neonatal infection and maternal–fetal blood group incompatibility are the leading causes of early and severe indirect hyperbilirubinemia and are associated with an increased risk of exchange transfusion in neonates.